2022
DOI: 10.1177/11772719221128145
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Post-Brain Injuries By Measuring Plasma Levels of Neuron-Derived Extracellular Vesicles

Abstract: Background: Extracellular vesicles (EV) released from neurons into the blood can reflect the state of nervous tissue. Measurement of neuron derived EV (NDE) may serve as an indicator of brain injury. Methods: A sandwich immunoassay was established to measure plasma NDE using anti-neuron CD171 and anti-EV CD9 ([CD171 + CD9+]). Plasma samples were obtained from commercial sources, cross-country (n = 9), football (n = 22), soccer (n = 19), and rugby (n = 18) athletes over time. Plasma was also collected from pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 23 publications
(34 reference statements)
2
7
0
Order By: Relevance
“…The protocol for the double label sandwich ELISA immunoassay in this study is similar to a previous publication 21 which demonstrated the size (100–200 nm, consistent with small EVs) and electron micrographic characterization of NDEs using this method. In the current study, EV data represent the double label of the CD171 NDEs or EAAT1 ADEs or MOG ODEs with the CD9 common EV marker.…”
Section: Methodssupporting
confidence: 78%
See 2 more Smart Citations
“…The protocol for the double label sandwich ELISA immunoassay in this study is similar to a previous publication 21 which demonstrated the size (100–200 nm, consistent with small EVs) and electron micrographic characterization of NDEs using this method. In the current study, EV data represent the double label of the CD171 NDEs or EAAT1 ADEs or MOG ODEs with the CD9 common EV marker.…”
Section: Methodssupporting
confidence: 78%
“…A prior study used control plasma samples applied to anti-L1CAM (neuronal marker) and anti-CD81 (common EV marker 35 ) immobilized ELISA wells. Subsequently the ratio of various other anti-neuronal and anti-non-neuronal antibodies were used to compare the two well types 21 . The ratio of these antibodies in anti-L1CAM versus anti-CD81 wells was high for neuronal markers (S100B, AchE, NRGN, CTSD, SV2A, SYNPO, SNAP25) and low for non-neuronal markers (CD9, GAPDH, ALDO, SFTPB, PSEN, BACE).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When we tested 63 control plasma samples, values were widely distributed over 2 logs (Supplemental Fig. 1), similar to our previous studies on neuron-derived EV (10). Thus, as shown in the next section, we focused on the longitudinal studies.…”
Section: Resultssupporting
confidence: 57%
“…Plasma samples from high school cross-country and American football players (Indiana University, Bloomington, IN), ice hockey (University of Louisiana at Lafayette, Lafayette, LA), and college rugby (Keio University, Kanagawa, Japan) were the same as our previous studies (10)(11) with additional samples of cross-country and football from different high schools. Detail of these samples were described in the Results of those studies (10)(11). For capillary blood collection, we used Tasso device (Seattle, WA) in Fig.…”
Section: Methodsmentioning
confidence: 99%